Welfare, una propuesta sostenible para mejorar la calidad de salud mental de las personas de la ciudad de Lima - Evangelista Armijo, Gina Patricia (2025)
According to the Institute of Health Metrics and Evaluation, around the world in 2019, one in eight people lives with mental disorders, with anxiety and depression disorders being the most common. According to the World Health Organization (WHO-WHO), in 2020, the number of people living with anxiety and depression disorders increased significantly due to the Covid-19 pandemic, whose figures initially show a 26% to 28% increase for anxiety and depressive disorders respectively, in just one year. According to the Peruvian Ministry of Health, two out of every ten Peruvians suffer from some mental disorder. For this reason, a study was carried out through surveys of people who live in the Miraflores district and with an age range of between 25 and 50 years. It was identified that the relevant social problem is that people from the A, B, C socioeconomic sector from 20 to 50 years old in Miraflores and similar districts of Lima Top do not find mental health treatment services that cover their needs in a comprehensive and effective manner. Likewise, there is a low percentage of people who suffer from these disorders and who go to an appointment with a professional. In line with the aforementioned, a virtual platform called “welfare” is proposed, which means: “wellbeing” whose purpose is to provide a communication channel so that anyone suffering from these disorders can access information, access specialized medical treatment and a holistic solution. The five-year financial viability results of the Welfare project indicate that it is financially viable, because it generates a financial net present value (NFPV) of S/ 3’790,317.82, with an (IRR) of 201%. Likewise, it generates a Social NPV of S/ 6’168,928.16, which represents a relevance index with respect to SDGs No. 3 and No. 8 of 38.5%. In this way the project generates continuous benefit to society, as well as to shareholders.